2022
DOI: 10.3390/nu14061243
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Related Brain Cholinergic System Impairment in High-Fat-Diet-Fed Rats

Abstract: A link between obesity and cerebral health is receiving growing recognition. Here, we investigate in the frontal cortex and hippocampus the potential involvement of cholinergic markers in brain alterations previously reported in rats with obesity induced by diet (DIO) after long-term exposure (17 weeks) to a high-fat diet (HFD) in comparison with animals fed with a standard diet (CHOW). The obesity developed after 5 weeks of HFD. Bodyweight, systolic blood pressure, glycemia, and insulin levels were increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
(115 reference statements)
1
7
0
Order By: Relevance
“…After 17 weeks of HFD, animals were sacrificed, and heart weights were recorded. Blood parameters were reported previously as well as systolic blood pressure [26,[32][33][34][35][36]. DS and DJS groups presented a decrease in systolic blood pressure in comparison with DIO rats.…”
Section: Animal and Blood Parameterssupporting
confidence: 61%
“…After 17 weeks of HFD, animals were sacrificed, and heart weights were recorded. Blood parameters were reported previously as well as systolic blood pressure [26,[32][33][34][35][36]. DS and DJS groups presented a decrease in systolic blood pressure in comparison with DIO rats.…”
Section: Animal and Blood Parameterssupporting
confidence: 61%
“…Following the results carried out in DIO subjects (Silva et al ., 2019), we found that the M 1 , but not M 3 mAChR, was significantly reduced in the hippocampus of MSG-obese rats. Interestingly, the hippocampus of DIO rats had no change in the expression of M 1 , M 3 , and M 5 mAChR subtypes for 5 or 17 weeks (Martinelli et al ., 2022). On the other hand, 20-week-old obese Zucker rats only had reduced M 1 but not reduced M 3 subtype in the hippocampus (Martinelli et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In older adults, obesity was also associated with reduced the brain’s gray matter (Beyer et al, 2019), which mediated lower memory performance (Kharabian Masouleh et al, 2016). Obesity may also lead to abnormal changes in the brain white matter (Daoust et al, 2021), cholinergic signaling system (Martinelli et al, 2022), and importantly, the hippocampal structure or functions that support memory processing (Parent et al, 2022). These effects may be caused by the low-grade inflammation, metabolic disturbances, or cerebro-microvascular impairment due to obesity (Balasubramanian et al, 2021; Buie et al, 2019; Spyridaki et al, 2016).…”
Section: Discussionmentioning
confidence: 99%